2018
DOI: 10.1016/j.joen.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photodynamic Therapy on the Adhesive Interface of Fiber Posts Cementation Protocols

Abstract: PDT presented negative effects on the bond strength to dentin in the cervical third after cementation using Relyx ARC and on the dentinal penetrability of the etch-and-rinse adhesive system in the cervical and apical thirds of the prosthetic space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
2
27
0
3
Order By: Relevance
“…However, this was not observed in our study using laser confocal microscopy. Our results are in agreement with previous research, which observed the low formation of the hybrid layer and dentin penetrability (Cerqueira et al, ; Ramos et al, ). Consequently, the adhesion between Relyx U200 and GC Gold Label 1 with root dentin is mainly caused by direct chemical bonding (D'Alpino et al, ; McLean & Wilson, ; Ramos et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, this was not observed in our study using laser confocal microscopy. Our results are in agreement with previous research, which observed the low formation of the hybrid layer and dentin penetrability (Cerqueira et al, ; Ramos et al, ). Consequently, the adhesion between Relyx U200 and GC Gold Label 1 with root dentin is mainly caused by direct chemical bonding (D'Alpino et al, ; McLean & Wilson, ; Ramos et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…The bond strength of a material to the dentin substrate indicates the magnitude of adhesion that occurs at the adhesive interface (Ramos et al, ; Victorino et al, ). In our study, the chemically activated glass ionomer cement showed similar results to the self‐adhesive resin cement (Relyx U200), regardless of the third of the root that was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that PDT decreased bond strength values in the coronal region while showing similar values in the apical and middle thirds. Our results are similar to those found in that study, which used laser devices with 780-808-nm wavelengths and a 0.005% methylene blue dye (26). We concluded that the decrease in our study was due to the difficulty of removing the smear layer in the apical region, the decreasing number of dentine tubules toward the apical region, and the connection surface area being smaller in the apical region.…”
Section: Discussionsupporting
confidence: 90%
“…The positive effect of photodynamic therapy can also extend to adhesion when used as a decontamination protocol before cementation. We did not find any studies able to reveal the impact of PDT on prosthodontic cementation, while in endodontics and orthodontics, it had a negative impact or was effectless on the bond strength and mechanical properties of dentin from the intracanal prosthetic space [ 8 , 9 , 10 , 11 ] and bond strength of orthodontic brackets [ 12 ].…”
Section: Introductionmentioning
confidence: 99%